How to know the freshwater crustacea - Fitzpatrick jr., Joseph F. (Estados Unidos | ESTADOS UNIDOS C. Brown Company / Washington, 1983)
Contents: The class crustacea; How to use key; General references and literature; Key to the families and higher taxa; Keys to Geneva and species
Sin Especificar
Keywords: Crustacea-Agua dulce